Formal versus informal: Efficiency, inclusiveness, and financing of dairy value chains in India - Chand, Ramesh; Joshi, Pramod Kumar; Saxena, Raka; Rajkhowa, Pallavi; Khan, Md. Tajuddin; Khan, Mohd. Arshad; Chaudhary, Khyali R.; Birthal, Pratap Singh (International Food Policy Research Institute, 2016)
Despite a growing dairy industry in India, farmers’ lack of access to organized markets and institutional credit remains one of the major hindrances in improving the scale and productivity of dairying. Using data from a survey of 612 households from the state of Punjab, India, this paper evaluates farmers’ choices of dairy value chains and their financing mechanisms. The study finds that 62 percent of the sample farmers representing 69 percent of the total milk sales are connected with formal value chains driven by cooperatives, multinational companies and private domestic processors. Small dairy farmers are associated more with informal value chains but they are not excluded from the formal value chains. The performance of different value chains in terms of productivity and profitability of dairying is almost on par. Also, there is hardly any difference in the milk price offered by formal and informal buyers pointing towards milk market being competitive. More than half of the farmers borrow credit both from within and outside the chain for dairying related activities. Chain-based financing is restricted to only one-fourth of the borrowers and mostly to those associated with informal value chains. Financing by commercial banks and other financial institutions is limited to only 9 percent of the borrowers, mainly larger farmers. The socially-disadvantaged and smallholder farmers are often neglected in institutional lending because of their lack of physical assets to use as collateral against loans. Value chain approach, due to its product market orientation, can serve as an entry point for financial institutions to improve their outreach to smallholders. The innovative financial products, such as ‘dairy credit card’ and ‘contract as collateral’ would enable them to adopt yield-enhancing technology and inputs and also to scale up their dairy activity.